2016
DOI: 10.21767/2171-6625.1000156
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Making in Adolescents According to Reaction Time, HEG and PASS

Abstract: Background: The Planning, Attention, Simultaneous and Successive (PASS) theory of intelligence allows us cognitive assessment. Hemoencephalography (HEG) allows us to assess cortical prefrontal activity. Reaction time (RT) allows us to assess decision-making. We aim to find teenager profile according to the PASS, HEG, and RT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…The hypothesis was that the rating condition suggested that individual differences in cerebral blood flow were large and varied. With respect to the relationship between the physiological index and the personality traits, this study determined that physiological individual differences affected the results of the experiment (Eysenck, ; Perez‐Alvarez, Serra‐Sala, & Timoneda‐Gallart, ). Furthermore, this experiment also concluded that the variation in cerebral blood flow, as presented in Figures and , revealed individual differences in frontal blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis was that the rating condition suggested that individual differences in cerebral blood flow were large and varied. With respect to the relationship between the physiological index and the personality traits, this study determined that physiological individual differences affected the results of the experiment (Eysenck, ; Perez‐Alvarez, Serra‐Sala, & Timoneda‐Gallart, ). Furthermore, this experiment also concluded that the variation in cerebral blood flow, as presented in Figures and , revealed individual differences in frontal blood flow.…”
Section: Discussionmentioning
confidence: 99%